Looking for Lukács: Examining Five GDR Novels in Translation - Kendall, Simon (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2022)
Certain translations into English published in the German Democratic Republic (GDR), the Socialist German state that existed from 1949 to 1990, have attracted attention both from translation scholars and literary translators. In particular, a 1965 translation by Joan Becker of Christa Wolf’s Der geteilte Himmel has been subject to several articles as well as study in two previous graduate dissertations, as scholars have there identified what has been understood to be traces of censorship and/or Lefeverian patronage and rewriting. This dissertation expands upon previous research in this area, and encompasses a wider sample of translations from the GDR-based Seven Seas Publishers, in order to assess whether the tendencies studied in the Becker translation were representative of a broader culture of translation and strategies shared by multiple translators from the era. The findings indicate that previous studies may have ‘overfit’ aspects regarding a GDR ‘style’ of translation, but reaffirm their broader conclusions about the outcome of GDR patronage on translation.
Keywords: Literary Translation